The Effect of Organizational Culture and Job Satisfaction on Entrepreneurship in MSMEs in Bogor - Hidayati, Nanda; Nutosudjono, Didik; Sunaryo, Widodo (Westscience Press, 2023)
This study explores the relationship between organizational culture, job satisfaction and entrepreneurship in Micro, Small and Medium Enterprises (MSMEs) in Bogor Regency. Using a diverse sample of 225, the study employed quantitative analysis to test the relationships among the variables. Findings indicated a strong positive relationship between a supportive organizational culture and increased entrepreneurial activities. Moreover, job satisfaction emerged as an important mediator in this relationship, emphasizing the importance of employee well-being in fostering an intrapreneurial mindset. This research contributes to theoretical understanding by aligning with innovation theory, emphasizing micro-level dynamics within the entrepreneurial ecosystem, and providing insights for practical application within the MSME sector.